Design for Android-Based Virtual Tour Application Using Polygonal Modeling and Extrude Face - Syarifah Eiva; Muhammad Iqbal (JAIA - Journal of Artificial Intelligence and Applications, 2020)
STMIK Amik Riau is the first Computer College in Riau under the Kopertis Region 10 which has an activity based on the information technology sector. This certainly requires the campus management to take advantage of technological developments in every academic activity. STMIK Amik Riau has quite a lot of facilities and infrastructure to support academic activities. However the problem is that the introduction to campus area system has not followed the current competition trend, because the campus introduction system used is still web-based and utilizes social media such as Facebook and Instagram. In order to improve the services of the campus, a virtual tour application that presents android-based campus area information is designed. This application is designed android based by using Polygonal Modeling and Extrude Face Polygonal modeling is an approach to modeling objects using points that determine the area of ​​a surface so that it can create fields from three-dimensional (3D) models. With the application of Android-based technology, the resulting application is expected to be easily accessed because almost all levels of society nowadays have used a Android smart phones. This certainly facilitates the public and students in obtaining information about the shape of the building and the area around campus